The relativistic attitude in development: reflections on the implementation of the Ethiopian multinational Constitution - Marco Bassi (Archivio Antropologico Mediterraneo)
Under the development approach that targets economic growth as its sole objective the marginalised groups may seriously be impacted. The developmental policy adopted since 1991 in Ethiopia illustrates it in relation to small-holding farmers, pastoralists and ethnic minorities. At the international level, alternative development paradigms have evolved along with progress in human rights. This article shows that the corrective measures have been informed by a growing ‘relativistic’ attitude, consisting in giving consideration to the relevance of specific articulations of culture, formal or informal norms and local conditions. The relativistic attitude is first defined and then considered in terms of compatibility with the Ethiopian multinational Constitution, adopted in 1995 but never really implemented. Under the pressure of the Qeerroo movement the ruling coalition in Ethiopia is today opening up to democracy and effective decentralisation. There is today a concrete possibility to revise the country’s developmental policy, in line with the Constitution and respecting second and third generation human rights.